Digital watermarking for digital images using wavelet transform - Yusof, Yusnita; Khalifa, Othman Omran (2007)
The field of digital watermarking has recently seen vast interests covering theoretical studies, novel techniques, attacks and analysis. This is due to the fact that over the last 15 years, the watermarking community has focused on developing and introducing new techniques for watermark embedding and detection. Analysis of these techniques leads to methods for attack and development of countermeasures which then used to discover faults and limitations in applications, encouraging the development of better ones. In this paper, comprehensive overview of digital watermarking are discussed. This includes the general model, types, applications and future trends of current implementations. The proposed technique is described and analyzed. The paper concludes with future plans of the chosen method in digital watermarking.